The role of manganese superoxide dismutase in skin aging - Treiber, Nicolai (Landes Bioscience, 2012)
The free radical theory of aging postulates that the production of mitochondrial reactive oxygen species is the major determinant of aging and lifespan. The skin represents an excellent and accessible model organ to study aging that is characterized by atrophy, wrinkle formation, reduced tensile strength and impaired wound healing. Oxidative stress as a consequence of an imbalance in prooxidants and antioxidants with increased ROS concentrations has been demonstrated in the aged skin in vitro and in vivo, suggesting the important role of the antioxidant balance. Here we will summarize recent data on the role of the mitochondrial superoxide dismutase 2 in skin aging.